The Effectiveness of Innovative Audio-Visual Media on the Listening Skills of Folk Tales of MI Miftahul Huda Students - Irfa Nur Amalia; Rini Azizah; Nurul Fahmi (Ihsan Cahaya Pustaka, 2025)
Listening skills are a fundamental component of language learning in Madrasah Ibtidaiyah, yet conventional methods often prove insufficient, particularly in fostering deep comprehension of folk tales. This study aims to examine the effectiveness of innovative audio-visual media in enhancing students’ listening skills at MI Miftahul Huda. Employing a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group type, the study involved 62 students divided into an experimental group ( ) and a control group ( ). Data were collected through listening skill tests and observation sheets, and analyzed using paired sample t-tests and independent sample t-tests. Results indicated a significant improvement in the experimental group (posttest mean ) compared to the control group ( ), with a statistically significant difference between groups ( ). These findings confirm that innovative audio-visual media create a contextual, engaging, and meaningful multisensory learning experience, enhancing comprehension and active participation. This study provides practical and theoretical contributions to the development of adaptive language learning strategies in the digital era.